Selective DNA amplification from complex genomes using universal double-sided adapters - Callow, Matthew J. (Oxford University Press, 2004)
There is a rapidly developing need for new technologies to amplify millions of different targets from genomic DNA for high throughput genotyping and population gene-sequencing from diverse species. Here we describe a novel approach for the specific selection and amplification of genomic DNA fragments of interest that eliminates the need for costly and time consuming synthesis and testing of potentially millions of amplicon-specific primers. This technique relies upon Type IIs restriction enzyme digestion of genomic DNA and ligation of the fragments to double-sided adapters to form closed-circular DNA molecules. The novel use of double-sided adapters, assembled through the combinatorial use of two small universal sets of oligonucleotide building blocks, provides greater selection capacity by utilizing both sides of the adapter in a sequence-specific ligation event. As demonstrated, formation of circular structures results in protection of the desired molecules from nuclease treatment and enables a level of selectivity high enough to isolate single, or multiple, pre-defined fragments from the human genome when digested at over five million sites. Priming sites incorporated into the adapter allows the utilization of a common pair of primers for the amplification of any adapter-captured DNA fragment of interest.